KUALITAS AIR WADUK PENJALIN BERDASARKAN STRUKTUR KOMUNITAS MAKROBENTHOS - Ratih Junika Widjaja Putri; Carmudi Carmudi; Anastasia Endang Pulungsari (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Macrobenthos is one of the biotic water constituent and can be used as bioindicator in determining water quality conditions. Water quality can be seen in terms of community structure of macrobenthos. The present study aimed to determine the physical and chemical water qualities in Penjalin Reservoir and to know the community structure of macrobenthos contained in the waters of Penjalin Reservoir. Community structure includes Density (organism/m2), Relative Density, Dominance Index (C) and Diversity Index (H ') as well as to determine the relationship between the water quality (physical and chemical) and the macrobenthos density. The physical and chemical qualities of Penjalin Reservoir water was good based on class III water quality standard according to PP No. 82 Ttahun 2001. Based on observation, 11 macrobenthos were obtained. Diversity Index (H') based on the criteria of Lee et al. (1978) showed moderate values (2.07 to 1.66) suggesting a low contamination level. The relationship of macrobenthos density and its chemical and physical quality of water pH, temperature, light penetration, depth, DO, BOD was weak, but had strong relationship with TSS. The results showed a linear regression equation Y = 898.76 X - 236.946 (Y = density and X = TSS) which could be interpreted that the more value of macrobenthos density the higher value of TSS contained in the water.